2022
DOI: 10.1186/s12888-022-04163-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporally ordered associations between type 2 diabetes and brain disorders – a Danish register-based cohort study

Abstract: Background Type 2 diabetes mellitus (T2DM) is linked with several neurodegenerative and psychiatric disorders, either as a comorbid condition or as a risk factor. We aimed to expand the evidence by examining associations with a broad range of brain disorders (psychiatric and neurological disorders, excluding late-onset neurodegenerative disorders), while also accounting for the temporal order of T2DM and these brain disorders. Methods In a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
(75 reference statements)
0
26
0
Order By: Relevance
“…A meta-analysis suggested a higher incidence and mortality from cardiocerebral vascular disease in people with severe mental illness than in those without ( 37 ). Some mental illnesses are associated with insulin resistance ( 38 , 39 ); patients with severe mental illness are more likely to develop diabetes with more severe and frequent microvascular and macrovascular complications, and insulin resistance may further contribute to hypertension, thereby increasing the risk of cardiocerebral vascular disease ( 40 ). In addition, a recent MR study suggested that mood swings are related to cardiocerebral vascular disease risk ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis suggested a higher incidence and mortality from cardiocerebral vascular disease in people with severe mental illness than in those without ( 37 ). Some mental illnesses are associated with insulin resistance ( 38 , 39 ); patients with severe mental illness are more likely to develop diabetes with more severe and frequent microvascular and macrovascular complications, and insulin resistance may further contribute to hypertension, thereby increasing the risk of cardiocerebral vascular disease ( 40 ). In addition, a recent MR study suggested that mood swings are related to cardiocerebral vascular disease risk ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity, defined as the co-occurrence of multiple conditions within an individual, poses substantial challenges to healthcare systems (Skou et al, 2022). An example is the observed co-occurrence of insulin resistance (IR)-related metabolic conditions, such as type 2 diabetes mellitus (T2DM), obesity, and metabolic syndrome (MetS), with neuropsychiatric disorders (Wimberley et al, 2022). This multimorbidity contributes to more severe physical and mental health outcomes, leading to reduced treatment effectiveness and higher mortality rates (Fanelli and Serretti, 2022; Kraus et al, 2023; Possidente et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Stratified analyses showed negative genetic covariances between schizophrenia and somatic insulinopathies through gene sets related to insulin signaling and insulin receptor recycling [14]. Strongest associations were confirmed between type 2 diabetes mellitus and schizophrenia spectrum disorder [15]. A cross-sectional study has shown differences in the composition of the gut microbiota between healthy individuals and patients with schizophrenia [16].…”
Section: Introductionmentioning
confidence: 99%